TRANSYLVANIA TOURISM SUSTAINABLE DEVELOPMENT: AN ARTIFICIAL STORAGE RESERVOIR AND NATURAL HELIOTHERMIC PERSPECTIVE - MIHAI VODA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
Surface water resources like the artificial storage reservoir lakes or the natural heliothermic Ursu lake are vital for Transylvanian sustainable development. However, Transylvanian water resources role for nature-based tourism consist in the environmental diversity of its river basins, adjusted through a various typology of structural interventions made for inhabitant needs and built for their community protection and wellbeing. My research show that the beauty of Transylvanian complex environments remained untouched by mass tourism, mainly because of the difficult road accessibility options, a problem that is continuously solved by the local communities through European and Governmental funds. I found that Transylvanian natural and artificial lakes can be used by local communities in collaboration with other responsible authorities as a base and important resource for tourism development. The key for success consist in a common approach regarding the exploitation of those water resources. Transylvania has diverse water resources that can be used for community based tourism development. My results demonstrate that local people have to understand the importance of unity in actions and common interest protection. Furthermore, as long as they act as a whole, for their community benefit, they will comprehend the interaction complexity of environmental factors from which the water element represents the quintessence of life.